Inequalities in school climate in California. Issue 2 (13th April 2015) - Jain, Sonia; Cohen, Alison K.; Huang, Kevin; Hanson, Thomas L.; Austin, Gregory
Abstract : Purpose: – School climate, or the physical and social conditions of the learning environment, has implications for academic achievement. The paper aims to discuss this issue. Design/methodology/approach: – The authors examine how school climate varies by school-level characteristics in California using administrative data and the California School Climate Survey. Findings: – Teachers/staff at secondary schools, schools in large cities, schools that serve low-income populations, Hispanic- and black-majority schools, and/or low-performing schools reported less positive school climates, including staff/student relationships, norms and standards, student facilitative behaviors, and perceived safety, than their counterparts, paralleling other education inequity trends. Originality/value: – The authors encourage educators and school leaders to use data-driven and evidence-based strategies to overcome systematic inequities in positive school climate in order to create social contexts that nurture students' academic progress and teacher retention particularly in historically under-resourced schools.